The Limits of Genetic Inquiry - Lappé, Marc (The Hastings Center report, 1987)
Within the next few years scientists will almost certainly have pieced together a broad map of the major gene locations on the twenty-three human chromosomes. The rapid unfolding of this new knowledge raises new questions: What limits, if any, should be imposed on its acquisition? Who should control the wealth of resulting data? How should it be used? If, because of a deep-seated need for certitude, many persons are likely to perceive a positive gene probe test as an indicator of biologic destiny, probes may acquire a misleading status in our medical armamentarium.